Transcriptome responses to Ralstonia solanacearum infection in tetraploid potato - Zhuo Chen; Shunwei Shao; Xi Zhu; Yu Zhang; Zhendong Lan; Hui Jin (Heliyon)
Potato (Solanum tuberosum) is an important global food source, the growth of which can be severely impacted by Ralstonia solanacearum bacterial infection. Despite extensive research, the molecular mechanisms of potato resistance to this pathogen are imperfectly known. Huashu No. 12, a tetraploid potato genotype, is highly resistant to R. solanacearum. We inoculate Huashu No. 12 and Longshu No. 7 (highly susceptible to R. solanacearum) with R. solanacearum to compare disease resistance in these two potato varieties. Huashu No. 12 has significantly higher resistance to R. solanacearum infection than Longshu No. 7, with increased lignin content, and an abundance of callose and strong autofluorescence in the phloem sieve tube. Enzymes (e.g., superoxide dismutase, catalase, peroxidase, phenylalanine ammonia-lyase, and polyphenol oxidase) contribute to R. solanacearum resistance in Huashu No. 12. Transcriptome sequencing reveals 659 differentially expressed genes between the two varieties, with the ethylene responsive factor family containing the most differentially expressed genes. Gene ontology and KEGG analyses provided further insights into the genetic basis and molecular mechanisms underlying plant defense against R. solanacearum disease. By demonstrating the importance of enzymes and differential gene expression in Huashu No. 12 resistance to R. solanacearum infection, the breeding of disease-resistant potato becomes increasingly feasible.